Expression of components involved in cholesterol homeostasis maintenance during experimental autoimmune encephalomyelitis in rat spinal cord - Todorovic, Smilja; Milosevic, Katarina; Milosevic, Ana; Janjic, Marija M.; Sokanovic, Srdjan J.; Savic, Danijela; Lavrnja, Irena (Folia Neuropathologica, 2025)
Dysregulations in cholesterol homeostasis contribute to the pathogenesis of multiple sclerosis (MS) and its best described animal model, experimental autoimmune encephalomyelitis (EAE). Cholesterol is an important component of myelin, which is necessary for signal transmission between neurons. Demyelination leads to the formation of oxysterols, degradation products of cholesterol that are ligands for nuclear liver X receptors (LXRs). Genes regulated by LXRs are involved in cholesterol efflux, absorption, transport, and excretion, which we investigated in this study. In this study, we detected changes in gene expression of Srebf1, Ldlr, Soat1, Abca1, Lrp1, and Npc1, all of which are important in the regulation of cholesterol homeostasis, during the course of EAE in male and female rats. In particular, differential expression of Srebf1, Ldlr, and Soat1 was observed in the spinal cord of male and female rats during EAE. Moreover, these genes are altered during EAE. In contrast, the expression of Abca1 and Lrp1 was significantly affected only by sex. In male animals, the expression of Npc1 is conspicuously reduced in EAE pathology. Thus, our study confirms the involvement of enzymes of cholesterol metabolism in the pathophysiology of EAE, with sex and disease progression affecting the expression of these genes. These findings may improve the understanding of neurodegenerative diseases associated with impaired lipid metabolism in the brain, such as MS/EAE.